Down from the Mountaintop : From Belief to Belonging. - Dolezal, Joshua A. (University of Iowa Press, 2014)
A lyrical coming-of-age memoir, Down from the Mountaintop chronicles a quest for belonging. Raised in northwestern Montana by Pentecostal homesteaders whose twenty-year experiment in subsistence living was closely tied to their faith, Joshua Doležal experienced a childhood marked equally by his parents' quest for spiritual transcendence and the surrounding Rocky Mountain landscape. Unable to fully embrace the fundamentalism of his parents, he began to search for religious experience elsewhere: in baseball, books, and weightlifting, then later in migrations to Tennessee, Nebraska, a.